Optimized cabinet parameters for drying lithium-ion batteries based on coupled fluid–thermal field analysis - Peng, Xuan; Wang, Zhaohui; Shen, Gang; Yang, Yong (Frontiers in Physics, 2023)
Hot-airflow desiccation is a commonly applied technique for drying lithium ion batteries. However, most drying cabinet designs currently suffer from poor efficiency because they evacuate steam by ejecting the hot air in the cabinet to the open air continuously. This can be addressed by closing and opening the cabinet periodically, where the temperature of the heating zone is increased as quickly as possible through internal air recirculation in the closed position, and the steam is ejected with the hot air only during the open period. Nonetheless, drying cabinet designs of this nature have been rarely subjected to numerical analysis based on computational fluid dynamics and heat transfer, and the design factors enhancing the rate of temperature increase during the closed period remain poorly understood. The present work addresses these issues by outlining a detailed numerical approach for simulating the airflow temperature of a drying cabinet during internal air recirculation in its closed position, and the characteristics of the airflow and the temperature distribution in the dryer are evaluated via transient fluid-thermal coupling analysis. The results of the numerical investigations indicate that the heating efficiency is substantially influenced by the inlet airflow velocity, the distance between the trays holding the batteries, and the size of the free space between the front door and the trays. The results demonstrate that the developed model provides a useful means of evaluating and optimizing the heating efficiency of these types of drying cabinets.